Confounding Factors Affecting the Emotional Intelligence Amongst Jordanian Nursing and Midwifery Undergraduate Students During the COVID-19 Pandemic's Outbreak: A Cross-Sectional Study Using USMEQ-i - Alnjadat, Rafi; Al-Rawashdeh, Ahmad (Frontiers in Psychology, 2021)
Objective: This aim of this study was to determine which variables from the demographic data most affect the EI regarding the COVID-19 outbreak and the lockdown amongst the nursing and midwifery students in Jordan. Background: Emotional intelligence (EI) is the ability to recognize, express, comprehend, motivate, influence and regulate emotions proposed the first EI model, which includes three constructs: emotion assessment and expression, emotion consumption and emotion control. During the COVID-19 outbreak and lockdown, face-to-face study methods have been replaced by online teaching, which has caused many psychological effects. Method: A cross-sectional approach was used to measure EI for nursing and midwifery students. The tool was completed online by nursing and midwifery students using Google Forms. All of the findings were received online and then analyzed accordingly. In this study, USMEQ-i was used to gather data from the participants. Results: The general EI score for the student respondents falls into the average score (M = 39.6). Regarding the difference between males and females, the results showed no significant difference. Moreover, the general linear regressions analysis of independent variables on EI score showed four significant factors. Nursing students who study in Years 1 and 4 had significantly higher EI scores than those in Years 2 and 3. EI ability decreased when a student's economic status changed from luxurious to middle income. Moreover, an increase in age significantly decreased the value of EI. This study indicates that all nursing and midwifery students who enrolled in general nursing program tended to have higher EI scores than others (p = 0.006). Conclusion: Year of study, age, average lifestyle and enrollment in a nursing program were found to be the most significant factors associated with EI amongst Jordanian nursing and midwifery students. This issue needs to be researched further, such that appropriate steps can be taken to address it.